(untitled) (Revista Interdisciplinar de Direitos Humanos, 2020)
This essay presents reflections to thematize a certain understanding of science and ethics. It does this by recovering critical elements from both the one and the other, and particularly the relationship between them. The concerns are in the context of the processes of coping with the Covid-19 pandemic. It is in a critical position both to anti-scientific positions and also to those who are adherents to a certain way of understanding science as absolute. It seeks to escape the dilemma that falsely separates the debate between “anti-scientific denialism” and “primary scientism”. In addition to the contextual aspects, it seeks to present alternatives. In an essayistic tone, criticizes the concept of traditional science, presents an alternative concept of science, discusses critically the idea of progress, of procedures, among other aspects. He defends the proposal of a new science and a new ethics. The background is made explicit by the presentation of the proposed understanding of human rights in crossing as part of this debate between ethics and science.